The Relationship Between the Intensity of Social Media Use and Self-esteem in Adolescents at SMK Kesehatan Kesatrian 2 Purwokerto - Carwati Carwati; Ita Apriliyani; Siti Haniyah (PROMOTOR, 2024)
Adolescence is a time of searching for identity and identity. Many adolescents experience mentally-related problems related to the maturation process such as self-esteem, where self-esteem is very important for adolescents in their development. Self-esteem is influenced by several factors, one of which is the use of social media. This study aimed to see if there was a relationship between the intensity of social media use and self-esteem in adolescents. This research method is descriptive correlational with a cross-sectional design. Samples of 91 students of SMK Kesehatan Kesatrian 2 Purwokerto class X and XI were taken using proportionated random sampling techniques. Data collection was carried out by distributing Social Network Time Usage Scale (SONTUS) and Rosenberg Self-Esteem Scale (RSES) questionnaires. The results of the Spearman test of social media use intensity and self-esteem obtained a p-value <0.05 with a correlation coefficient value of r = -0.267. The results of this study show a negative correlation between the intensity of social media use and self-esteem, meaning that the higher the use of social media, the lower self-esteem. Teenagers should use social media wisely to avoid its negative impact on self-esteem problems